2020
DOI: 10.1038/s41598-020-62209-2
|View full text |Cite
|
Sign up to set email alerts
|

Biotic and Abiotic Contribution to Diurnal Soil CO2 Fluxes from Saline/Alkaline Soils

Abstract: As the second largest carbon flux in terrestrial ecosystems, the soil CO 2 flux is closely related to the atmospheric co 2 concentration. the soil co 2 flux is the sum of biotic respiration and abiotic geochemical co 2 exchange; however, little is known about abiotic co 2 fluxes in arid areas. To investigate the relative contribution of abiotic and biotic soil co 2 fluxes over a diurnal course, the abiotic CO 2 flux was distinguished by autoclaving sterilization in both saline and alkaline soils at an arid sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…To determine the fractionation of SIC-derived CO 2 relative to SIC, it is important to eliminate the interference of SOC-derived CO 2 (Skidmore et al, 2004). Recently, a series of sterilization studies were conducted to partition the contribution of SIC to total soil CO 2 emissions by eliminating the microbial respiration process (Ma et al, 2017;Wang et al, 2020). Consequently, in future studies, isotope fractionation in δ 13 C values between SIC-and SIC-derived CO 2 should be measured by sterilization treatment.…”
Section: Possible Uncertainties In Partitioning Soil Co 2 Emissions By Three Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the fractionation of SIC-derived CO 2 relative to SIC, it is important to eliminate the interference of SOC-derived CO 2 (Skidmore et al, 2004). Recently, a series of sterilization studies were conducted to partition the contribution of SIC to total soil CO 2 emissions by eliminating the microbial respiration process (Ma et al, 2017;Wang et al, 2020). Consequently, in future studies, isotope fractionation in δ 13 C values between SIC-and SIC-derived CO 2 should be measured by sterilization treatment.…”
Section: Possible Uncertainties In Partitioning Soil Co 2 Emissions By Three Sourcesmentioning
confidence: 99%
“…In carbonate-rich soils, recent studies have found that soil-derived CO 2 emissions come not only from SOC decomposition but also from SIC dissolution. The contribution of SIC dissolution to soil C (SIC + SOC) release ranged from 3 to 95% in carbonate-rich soils without plants (Lardner et al, 2015;Schindlbacher et al, 2015;Wang et al, 2020). Therefore, SIC dissolution is more important to stabilize the global C pool and regulate atmospheric CO 2 concentrations than previously thought (Zamanian and Kuzyakov, 2019;Raza et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Maximum emissions of CO 2 from soils may occur during transient periods when multiple limiting resources become available to microorganisms (Choi et al, 2022;Seastedt & Knapp, 1993), suggesting that a combination of warmer and substrate-rich conditions could magnify soil CO 2 emission pulses. However, models of CO 2 emissions do not typically surpass 35°C (Davidson et al, 2012;Tian et al, 2015) and desert field studies show inconsistent soil respiration responses to higher temperatures, with some observing continued increases (Richardson et al, 2012;Zhang et al, 2010Zhang et al, , 2015 and others observing decreases (Leon et al, 2014;Wang et al, 2020) in CO 2 efflux at temperatures above 30°C. Simultaneously, soil CO 2 production generally increases with soil C concentrations (Eberwein et al, 2015;Evans et al, 2016), but this correlation may mask other factors that contribute to soil respiration such as root-microbe interactions (Ryan & Law, 2005) and soil stoichiometry (Choi et al, 2022;Liang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Soil CO 2 emissions comprise both biotic respiration related to SOC, and abiotic geochemical CO 2 exchange related to SIC (Wang et al, 2020). Incubation in a closed system is a common technique to measure CO 2 emission from soil (Pumpanen et al, 2000).…”
Section: Introductionmentioning
confidence: 99%